India Policy Insights: A geospatial and temporal data science and visualization platform and architecture - Devika Jain; Joaquin Kachinovsky; Gonzalo Rodriguez; Junyi Chen; Rockli Kim; S V Subramanian (SoftwareX)
The Geographic Insights Lab at Harvard University developed India Policy Insights (IPI), a spatio-temporal visualization platform for policymakers. IPI provides insights from 122 indicators across population, health, and socioeconomic metrics spanning 720 districts, 543 parliamentary constituencies, and 600,000 villages in India. Its applications include breastfeeding campaigns,policy development, and government reporting. It is fully deployed on Microsoft Azure using Docker, which ensures scalability and reproducibility. Built on an open-source stack with React,.NET, and PostGIS, it processes, stores, visualizes, and queries geospatial big data. This paper highlights IPI's architecture and methodologies for tackling public policy challenges.